Electrostatics Conceptual Test (ECT) as an Assessment Instrument for Undergraduate Student’s Conceptual Mastery on Static Electricity - Hasanah, Rizqiatul; Hidayat, Arif; Sutopo, Sutopo; Fawaiz, Sahal (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
This study aims to develop an assessment instrument for student mastery of the concept of static electricity, the